Internationally educated nurses' experiences in a hospital in England: an exploratory study. Issue 4 (21st November 2012) - Alexis, Obrey
Abstract : Background: The recruiting of internationally educated nurses (IENs) to work in the National Health Service (NHS) in the United Kingdom (UK) is not a new phenomenon. Such practices have its roots in the 1940s when the NHS was first incepted. Objective: The aim of this study was to gain an understanding of IENs' experiences of working in the NHS in England. Methods: Phenomenology in particular, Heidegger, was the approach adopted, and the study consisted of two phases in which twelve individuals' interviews were conducted in phase one. The findings from this phase informed the second phase where four focus group interviews were used. The data for both phases were thematically analysed. Results: Six themes emerged following data analysis, namely Leaving a familiar world, Being thrown into an unfamiliar world, Encountering marginalisation and experiencing inequalities in the world, Surviving in an everyday world, Living in an everyday world and Making a new world. Conclusion: Internationally educated nurses encountered a number of challenges to their working practices in an English hospital, and there is a need for both IENs and home‐grown nurses to adapt to each other cultural differences.